(untitled) (Global Journal of Management and Business Research, 2016)
Minority-owned businesses are not increasing in number since 2008 because the economy in the United States, and most of the world for that matter, are yet to recover fully. The period following the recession has been characterized by very high lending interest rates in different financial markets in the U.S. and the world over. Minority-owned businesses have been struggling to circumvent the high expenses of doing business as financial institutions try to recover from the catastrophic 2008 recession. The costs of acquiring resources necessary for production, too, have been increasing progressively, limiting the number of minority-owned businesses that can be established. The rapid flow of customers that existed before the 2008 recession, too, is yet to resume to its full capacity and the reduced demand has affected the emergence of new, minority-owned businesses (Brunner, 2007). Minority-owned businesses are also facing stiff competition from larger corporations that managed to stay virtually unaffected throughout the 2008 recession.